How does hybrid bridging core modification enhance the nonlinear optical properties in donor‐π‐acceptor configuration? A case study of dinitrophenol derivatives. Issue 2 (10th November 2014) - Muhammad, Shabbir; Irfan, Ahmad; Shkir, Mohd; Chaudhry, Aijaz R.; Kalam, Abul; AlFaify, Salem; Al‐Sehemi, Abdullah G.; Al‐Salami, A. E.; Yahia, I. S.; Xu, Hong‐Liang; Su, Zhong‐Min
Abstract : This study spotlights the fundamental insights about the structure and static first hyperpolarizability ( β ) of a series of 2, 4‐dinitrophenol derivatives (1–5), which are designed by novel bridging core modifications. The central bridging core modifications show noteworthy effects to modulate the optical and nonlinear optical properties in these derivatives. The derivative systems show significantly large amplitudes of first hyperpolarizability as compared to parent system1, which are 4, 46, 66, and 90% larger for systems2, 3, 4, and5, respectively, at Moller–Plesset (MP2)/6‐31G* level of theory. The static first hyperpolarizability and frequency dependent coupled‐perturbed Kohn–Sham first hyperpolarizability are calculated by means of MP2 and density functional theory methods and compared with respective experimental values wherever possible. Using two‐level model with full‐set of parameters dependence of transition energy (Δ Ε ), transition dipole moment ( μ 0 ) as well as change in dipole moment from ground to excited state (Δ μ ), the origin of increase in β amplitudes is traced from the change in dipole moment from ground to excited state. The causes of change in dipole moments are further discovered through sum of Mulliken atomic charges and intermolecular charge transfer spotted in frontier molecular orbitals analysis. Additionally, analysis of conformational isomers and UV‐Visible spectra has been also performed for all designed derivatives. Thus, our present investigation provides novel and explanatory insights on the chemical nature and origin of intrinsic nonlinear optical (NLO) properties of 2, 4‐dinitrophenol derivatives. © 2014 Wiley Periodicals, Inc. Abstract : A fundamental quantum chemical structure–property relationship spotlights the surprising effect of bridging core modification to robust nonlinear optical properties of dinitrophenol derivatives.